The Influence of Islamic Work Ethic, Productivity, and Employee Performance: Mediating Work Quality at KSPPS BMT - Abdullah Faiq; Muhammad Sholahuddin (UNIVED Press, 2024)
Islamic work ethic and productivity in the Islamic world play a crucial role in shaping individual character in the context of the world of work. The concept of Islamic work ethic is based on moral and ethical principles embodied in Islam, while productivity is an important factor in achieving individual and organizational goals., The research technique used is quantitative, with data collection using questionnaire methods, and the number of samples in this study is 110 employees. The analysis in this study was assisted using SmartPLS 3.0. The results showed that Islamic work ethic has a positive and significant effect on employee performance, productivity has a positive and significant effect on employee performance, Islamic work ethic has a positive and significant effect on work quality, productivity has a positive and significant effect on work quality, Islamic work ethic has a positive but not significant influence on work quality mediated by employee performance, Productivity has an effect on work quality mediated by employee performance, and employee performance has a positive and significant effect on work quality